Labor claims and certification in occupational health and safety management - Dionísio, Daniela (2018)
The main objective of this work is to evaluate the influence of the certification in safety and health management in workplaces in the accidents rates. To achieve this objective, a mixed research methodology was chosen: document analysis and questionnaire used as data collection techniques. The bibliographic review was carried out on the various aspects of Occupational Health and Safety (OHS) Certification and the questionnaire for the risk evaluation in OHS allowing work accidents and professional diseases identification. The developed questionnaire was distributed to both workers from companies with External OHS Service and from companies with Internal OHS Service, in a total of 74 questionnaires (60 and 14 respondents, respectively). Also, data on occupational accidents were used to gather information on OHS Services. The results of the study point out to an existing relationship between the type of OHS practiced/implemented in companies and the compliance with the statutory requirements of OHS, which may intervene directly in the workplace accidents. After analysing the studied variables, recommendations are proposed, aiming to an improvement of the OHS certifications.